The alter-imperial paradigm : empire studies and the book of Revelation - Wood, Shane J. (Biblical Interpretation Series, 2015)
Many assume the book of Revelation is merely an "anti-imperial" attack on the Roman Empire. Yet, Shane J. Wood argues this conclusion over-exaggerates Rome's significance and, thus, misses Revelation's true target-the construction of the alter-empire through the destruction of the preeminent adversary: Satan. Applying insights from Postcolonial criticism and 'Examinations of Dominance,' this monograph challenges trajectories of New Testament Empire Studies by developing an Alter-Imperial paradigm that appreciates the complexities between the sovereign(s) and subject(s) of a society-beyond simply rebellion or acquiescence. Shane J. Wood analyses Roman propaganda, Jewish interaction with the Flavians, and Domitianic persecution to interpret Satan's release (Rev 20:1-10) as the climax of God's triumphal procession. Thus, Rome provides the imagery; Eden provides the target.